Pengaruh Pelayanan Prima Front Dest Agent terhadap Kepuasan Tamu di The Zuri Hotel Pekanbaru - Lisa Lestari; Rusella wong; Sri Febdarina Febdarina; Maryantina Maryantina; Asur Suryana (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
This study aims to identify front desk agent human resources profile, describe Standard Operational Procedures implementation for excellent service, measure implementation level, and analyze the effect of front desk agent excellent service on guest satisfaction at The Zuri Hotel Pekanbaru. This study uses a mixed method combining qualitative and quantitative approaches. The qualitative approach explores HR profile and SOP implementation, while the quantitative approach measures excellent service effect on guest satisfaction. The research sample consisted of 104 hotel guests selected through purposive sampling and three key informants: one front office manager and two front desk agents. Data collection was conducted through questionnaires, in-depth interviews, and documentation. Data were analyzed using descriptive statistics and simple linear regression with SPSS version 29.0.1.0. Results indicate that front desk agents possess relevant hospitality education and adequate work experience. The implementation of excellent service SOPs is performed effectively through friendly greetings, magic words, welcome drinks provision, and personalized service. The excellent service implementation level is in very good category with average score of 4.27. Regression analysis shows that excellent service has positive and significant effect on guest satisfaction with coefficient of determination of 82.1 percent and t-value of 21.747 at significance level 0.05. Guest satisfaction level is in very satisfied category with average score of 4.29. This study recommends that hotel management optimize service quality through regular training and consider adding Guest Relations Officer to continuously improve guest loyalty.